The utility of universal screening for somatization in a pediatric emergency department: A prospective evaluation. (October 2021) - Virk, Punit; Ellis, Jacob; Dhariwal, Amrit; Chapman, Andrea; Doan, Quynh
Objective: To evaluate clinical utility and feasibility of universal somatization screening in the pediatric emergency department (ED) using a standardized approach of (1) identifying potential somatizing symptoms within the ED, (2) introducing these patients and their caregivers to the concept of the 'mind-body connection', (3) corroborating the likelihood of a somatization diagnosis via brief psychiatric assessment, and (4) inviting families to a psychoeducational follow-up session. Methods: We conducted a cross-sectional study to carry out this approach with families visiting a pediatric ED. Our primary outcome of screening utility was measured as the proportion of youth who screened positive for somatization by the ED clinician. Our secondary outcome of screening feasibility was measured as the proportion of patients with positives who (1) agreed to meet with the study psychiatrist, (2) consented to an ED psychiatric assessment, (3) were assessed by the study psychiatrist as likely experiencing somatization, and (4) were invited for follow-up and attended. Results: Of the 344 screened patients, 27 (7.8%) screened positive for somatization. Of these, 25 (92.6%) families verbally consented to meet the study psychiatrist to learn about the mind-body connection, and 21 (77.8%) consented to further psychiatric assessment. Upon assessment, the somatization likelihood was supported for all 21 youth. Twenty families were invited to follow-up and ultimately two (10%) attended. Conclusions: Somatization can be detected through ED-based universal screening. Few families attended psychoeducational follow-up. Further research is needed to determine appropriate ED-initiated pediatric somatization intervention.